Pengaruh Perceive Ease of Use dan Perceive Usefulness terhadap Minat Membeli Kembali Melalui Kepuasan Pelanggan pada menggunakan Aplikasi Online Shopping Di Kota Medan - Zahara, Mutia; Situmorang, Syafrizal Helmi (Peneliti.net, 2024)
This study aims to investigate how perceived ease of use and perceived usefulness contribute to customer satisfaction and their role in influencing the intention to repurchase through online shopping applications in Medan. Data was collected through a survey involving 150 active users of online shopping apps. Data analysis was conducted using the Structural Equation Modeling (SEM) approach with Partial Least Squares (PLS) technique. The results revealed that the ease of use of the application and the perceived benefits have a significant impact on customer satisfaction. Satisfaction serves as a mediator that facilitates the intention to repurchase. Furthermore, these two factors also indirectly affect repurchase intentions through customer satisfaction. The findings emphasize the importance of developing applications that are not only easy to use and intuitive but also provide clear benefits to users. This is crucial for enhancing satisfaction, strengthening loyalty, and building long-term relationships with app users. The practical implications of this study suggest that app developers should prioritize user-friendly interface design and offer meaningful added value. This is expected to strengthen long-term relationships with users and increase their intention to repurchase.